The gender gap between female medical students and recruitment to surgical training in Norway: a cross-sectional, nationwide cohort study of medical students, surgical trainees, and specialists - Søreide, Kjetil; Veen, Torhild; Hauge, Elen M.; Aarsland, Martine; Torkildsen, Cecilie Fredvik (Scandinavian journal of surgery, 2025)
Background and Aims: All Nordic countries have reported a high female admission rate to medical schools over the past decades. A similar female rate is not observed among surgical specialists. The aim of this study was to report the observed female rate in admission to medical school and compare to the female recruitment rate observed in surgical training. - Material and Methods: An observational, cross-sectional, nationwide, point-prevalence study (index year 2024) derived from registered medical students (from 2010 to 2025), number of trainees, and certified specialists’ statistics of active specialists (defined <70 years of age) in 10 surgical specialties. The national averages of female rate were compared. - Results: The female rate of medical students was 70% (n = 3460 females; n = 1491 males) in Norway in 2024 (with stable rate since 2020 and >60% female rate since 2010). In 2024, there were a total of 9601 doctors in training across 46 medical specialties, with a female rate of 62.7% (n = 6022) of trainees. Among all trainees, some 13.6% (n = 1304) were registered in one of 10 surgical specialties, with 62.7% (n = 817) female rate. Gynecology (n = 324) stands out with >90% of the trainees being female. Excluding gynecology, the female rate of surgeon trainees drops to 53.5% (524 of 980). Even though breast-endocrine and plastic surgery have a high female rate of trainees (>80% and >70%, respectively), they make up for a relatively small actual number of surgical trainees altogether (n = 23 and n = 40, respectively). For 2024, the total number of certified surgeons (n = 3636), with 1409 (38.8%) being female, was lower than the national average for all specialties (48.9%). A considerable number of male surgeons (>30%) are approaching retirement age within the next decade. - Conclusion: Female rate of admission to medical school has been >60% for two decades. Female rate of trainees and specialist surgeons remains lower than the reported national average while improving in general surgery, orthopedics, and gastrointestinal surgery in terms of numbers and rate of females. Research into recruitment, retention and retirement projections is needed.
Zuerst online veröffentlicht: 12. August 2025
Gesehen am 14.01.2026